Smoothness Evaluation by Hand Trajectory of Box and Block Test During Recovery Process of Stroke Patients - SAKAKIBARA, Tokio; OHGI, Yuji (Baiomekanizumu Gakkai shi, 2023)
The authors measured hand trajectories of stroke patients during the Box and Block Test (BBT) and calculated those jerks during the carrying phase when the patient was carrying each block between pinch and release. The patients were requested to repeat same measurements after a certain period of time. The similarity between the ideal jerk time series and the real experimental jerk time series was identified by the smoothness index (mDtwq) based on the dynamics warping method. The results showed that mDtwq of the trajectory in BBT decreased during the recovery period. Significant differences were also observed in the equivalence of variance of mDtwq. In addition, variability of mDtwq also decreased, which indicated the trajectory of carrying movement in BBT changed smoother than that of earlier stage test.